Third European Quality of Life Survey. Quality of life in Europe: families in the economic crisis - Sándor, Eszter; Ahrendt, Daphne; Kuenzi, Rachel (Luxembourg, 2012)
"The economic crisis has reshaped the lives of millions of European citizens. But how has it affected families with children? Children are more at risk of poverty or social exclusion than the overall population in a large majority of EU countries; hence, it is important to understand how the crisis has affected the households in which these children grow up. This report describes the changing quality of life across the EU for different types of families with children and compares their living standards and social situation. Grouping the EU Member States into four categories on the basis of the flexibility or otherwise of their family policies, it also examines potential patterns that may be related to different family policy approaches. Themes that emerge from the findings include the particular challenges facing lone parents, the greater difficulties facing jobless families since the onset of the crisis, and the increasing extent of conflict parents experience in seeking to balance their work and family lives"